Analysis of Cattle Food Pollard Cap Angsa Marketing Strategies on Sales to Distributors in the East Java Region - Sugiono, Sugiono; Alimudin, Arasy; T. Ade, Reswanda (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: The sales data for Pollard Cattle Feed cap angsa shows that turnover from 2020 to 2021 has decreased by IDR. 119.251.222. This shows that there are problems at the level of consumer purchasing decisions which result in a decrease in consumer interest in shopping, resulting in a decrease in turnover. By looking at the economic conditions and the business world during the current Covid-19 pandemic, Pollard Cattle Feed cap angsa after the Covid 19 Pandemic. The aim of this research is to find out the marketing strategies carried out after Covid 19 to increase sales of Pollard Cattle Feed cap Angsa. Design/methodology/approach: The type of research used in this research is a qualitative descriptive research method. Researchers collected primary data directly through observation and interviews with the owner of the research location, that is Polard Cattle Feed, sales officers for Polard Cattle Feed, and 3 consumers of Polard Cattle Feed. The data analysis method used in this research is SWOT analysis. Findings: Based on the results of the SWOT analysis, it shows that the marketing strategy used by Polar Cap Goose Cattle Feed for sales to distributors in the East Java region is: Product strategy based on SWOT Analysis and SWOT Matrix, especially in the market in the East Java region where products are in great demand with a score of 0.573 which makes it easier for the company to develop its product strategy by maintaining the quality of its products. Polar stamp distributor price strategy for increasing sales is based on maintaining higher prices. from competitors with a score of 0.309 due to the existence of a product that is highly sought after by consumers with a score of 0.573 then improving good cooperative relations with sub distributors and agents by providing feed prices in accordance with market prices. The promotion strategy is that the population of cattle and pigs is increasing as shown by the highest weight score is 0.576. However, the main threat faced by the company is the large amount of competition with a score of 0.476, and demand from foreign industry with a score of 0.650, the difficulty of keeping up with market prices with a score of 0.415. Based on the SWOT matrix, the WO strategy is used by increasing promotions to agents close to breeders. The distribution strategy of the research results shows that external factors, that is opportunities that can be achieved by companies where the number of competitors from similar companies is getting higher with a score of 0.476 and the weakness of higher prices with competitors with a score of 0.309 needs to be minimized by utilizing the strength of distributor locations close to consumers with a score 0.672 so that the strategy that can be carried out is to collaborate with sub distributors and agents in distributing factory DO to distributors closest to consumers Research limitations/implications: This research is limited to distributors who sell polar goose stamp cattle feed in the East Java region. Practical implications: That can increase sales of polar cattle feed cap angsa with building good relationships with customers, Originality/value: The findings from this research are new discoveries in marketing strategies the agents who are close to the breeder community through regular visits, and providing competitive prices that can be accepted by customers. Paper type: Research paper